A measure of human development - Dinzhanova, G. (BUKETOV BUSINESS REVIEW, 2021)
Object: The paper aims to define the appropriate approach to measuring human development in Kazakhstan. A new approach to human capital measurement is proposed. Methods: We used statistical data analysis, index calculation method, method of UNDP, and method of correlation and regression analysis. The sample mean method is used in the calculation of average national test results. Results: Results indicate the level of human development in the regions of Kazakhstan, including the level of health, education and life. Also, we have discovered the interrelation of human capital and the average income of the population. Conclusion: This article investigates the components of human capital development index, the computing of human development within Kazakhstan and its regions, relationship of the human development to income. The effect of income on HDI is explained in the article. The human capital index in Kazakhstan is high, however, in 6 regions it is average.